O processo sol-gel: uma visão físico-química - Hiratsuka, R. S. (1995)
The aim of this work was to revise the main concepts involved in the physical-chemistry of the sol-gel process. First, the preparation and its influence on the gel's structure are focalized; the sol-gel transition is revised under the thermodynamics of crytical phenomena point of view and by considering the kinetic models of aggregation. Second, the experimental methods usually used to characterize the sol-gel transition are discussed.